Mutations in TP53 increase the risk of SOX2 copy number alterations and silencing of TP53 reduces SOX2 expression in non-small cell lung cancer. Issue 1 (December 2016) - Samulin Erdem, Johanna; Skaug, Vidar; Bakke, Per; Gulsvik, Amund; Haugen, Aage; Zienolddiny, Shanbeh
Abstract Background Amplifications of the transcription factor, SRY (sex determining region Y)-box 2 (SOX2 ), are common in non-small cell lung cancer (NSCLC). SOX2 signaling is important in maintaining the stem cell-like phenotype of cancer cells and contributes to the pathogenesis of lung cancer. TP53 is known to inhibit gene amplifications and to repress many stem cell-associated genes following DNA damage. The aim of this study was to investigate ifTP53 mutational status affectedSOX2 copy number variation and gene expression in early-stage NSCLC patients; moreover, to assess if TP53 regulates SOX2 expression in human lung cancer cells. Methods 258 early-stage lung cancer patients were included in the study. Exons 4–9 in theTP53 gene were sequenced for mutations in tumor tissues.SOX2 copy number as well as TP53 and SOX2 gene expression were analyzed in tumor and in adjacent non-tumorous tissues by qPCR.TP53 andSOX2 were silenced using gene-specific siRNAs in human lung adenocarcinoma A427 cells, and the expression of TP53, SOX2 and subset of selected miRNAs was analyzed by qPCR. The odds ratios (ORs) for associations between copy number variation and lung cancer were estimated by conditional logistic regression, and the correlation between gene status and clinicopathological characteristics was assessed by Chi-square or Fisher's exact test. Gene expression data was analyzed using nonparametric Mann–Whitney test. Results TP53 mutations were associated with an increased risk of acquiring aSOX2 copy number alteration (OR = 2.08, 95 % CI: 1.14–3.79, p = 0.017), which was more frequently occurring in tumor tissues (34 %) than in adjacent non-tumorous tissues (3 %). Moreover, SOX2 and TP53 expression levels were strongly correlated in tumor tissues.In vitro studies showed that a reduction in TP53 was associated with decreased SOX2 expression in A427 cells. Furthermore, TP53 knockdown reduced the miRNA hsa-miR-145, which has previously been shown to regulate SOX2 expression. Conclusions TP53 signaling may be important in the regulation ofSOX2 copy number and expression in NSCLC tumors, and the miRNA hsa-miR-145-5p may be one potential driver. This prompts for further studies on the mechanisms behind the TP53-induced regulation of SOX2 expression and the possible importance of hsa-miR-145 in lung cancer.